Analysis of the Sharia Compliance Level of Murabaha Contracts on Non-Financial Performance in Sharia Banks - Kartini; Masriani; Niluh Anik Sapitri (Universitas Islam Negeri (UIN) Walisongo Semarang, 2026)
Purpose - This study aims to analyze the influence of the level of sharia compliance in the implementation of murabaha contracts on the non-financial performance of Islamic banks, especially in shaping customer trust, customer loyalty, and institutional reputation. Method - This study adopts a qualitative-descriptive approach using library research methods. Data was collected from indexed national and international academic journals, authoritative regulations, and related fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) published in the last five years. Data were analyzed using content analysis techniques to identify patterns, theoretical-practical gaps, and conceptual relationships between research variables. Result - Findings show that substantive sharia compliance in Murabaha contracts characterized by real ownership of transaction objects, transparency of pricing and profit margins, and active supervision by the Sharia Supervisory Board has a significant positive effect on customer trust, customer loyalty, and reputation of Islamic banks. On the other hand, compliance that is only administrative tends to weaken the integrity felt by Islamic banking institutions. Implication - These results highlight the importance of strengthening sharia governance, increasing the active role of the Sharia Supervisory Board, and improving customer sharia literacy as a strategic effort to maintain the non-financial performance of sharia banks. Practically, the findings provide valuable insights for regulators and practitioners in improving the quality and consistency of murabaha contract implementation. Originality - The originality of this research lies in its conceptual mapping that integrates sharia murabaha compliance with non-financial performance from a value-based perspective, thus contributing theoretically and reflectively to the development of sharia banking studies based on maqashid al-sharia. Keywords: Sharia Compliance, Murabaha Contracts, Non-Financial Performance, Sharia Banking, Customer Trust